Advancing precision in histocompatibility and immunogenetics: a comprehensive review of the UCLA exchange program - Zhang, Qiuheng; Locke, Arlene F.; Alvarez, Andrea Carolina; Cabarong, Maria L.; Liv, Lek Ching; Alfaro, Belen Garcia P.; Gjertson, David W.; Reed, Elaine F. (Frontiers in Genetics, 2024)
Precise typing of human leukocyte antigens (HLA) is crucial for clinical hematopoietic stem cell and solid organ transplantations, transfusion medicine, HLA-related disease association, and drug hypersensitivity analysis. The UCLA Cell Exchange program has played a vital role in providing educational and proficiency testing surveys to HLA laboratories worldwide for the past 5 decades. This article highlights the significant contribution of the UCLA Cell and DNA Exchange Programs in advancing HLA antibody testing, genotyping, crossmatches, and, more recently, virtual crossmatches. Additionally, we discuss future directions of the UCLA Cell Exchange program to support histocompatibility testing to adapt to the fast-evolving field of immunotherapy, tolerance and xenotransplantation.